The Novel Compounds with Biological Activity Derived from Soil Fungi in the Past Decade - Zhang D; Li S; Fan M; Zhao C (Dove Medical Press, 2022)
Danyu Zhang,1 Shoujie Li,1 Mohan Fan,2 Changqi Zhao1 1Gene Engineering and Biotechnology Beijing Key Laboratory, College of Life Science, Beijing Normal University, Beijing, People's Republic of China; 2Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People's Republic of ChinaCorrespondence: Changqi Zhao, Tel +86-5880-5046, Email 04020@bnu.edu.cnAbstract: The secondary metabolites isolated from soil fungi have received more and more attention, especially new compounds that exhibited good biological activities. In this review, a total of 546 new compounds are included in the relevant literature since 2011. The new compounds are isolated from soil fungi, We divided these compounds into seven categories, including alkaloids, terpenoids, steroids, ketones, phenylpropanoids, quinones, esters, lactones, etc. In addition, the biological activities and structure-activity relationships of these compounds have also been fully discussed. The activities of these compounds are roughly divided into eight categories, including anticancer activity, antimicrobial activity, anti-inflammatory activity, antioxidant activity, antiviral activity, antimalarial activity, immunosuppressive activity and other activities. Since natural products are an important source of new drugs, this review may have a positive guiding effect on drug screening.Keywords: soil fungi, new compounds, chemical structure, biological activity